Shear behaviour of steel fibre reinforced self-consolidating concrete beams based on the modified compression field theory - Ding, Yining (2012)
A series of steel fibre reinforced self-consolidating concrete (SFRSCC) beams have been tested to investigate the influence of steel fibres and the combined effect of fibres and stirrups on the deflection and cracking, ultimate loads and failure pattern. The experiment indicates that the shear strength increases clearly with the increasing of fibre content. The combination of steel fibres and stirrups demonstrates a positive composite effect on the ultimate load, ductility and failure pattern of concrete beam. This study also examines the feasibility of applying the modified compression field theory (MCFT) for the suitable assessment of shear resistance in fibre and steel rebar reinforced self-consolidating concrete beams. For fibre reinforced concrete member, a theoretical method is proposed based on the MCFT. The proposed ultimate shear capacity model was verified by the comparison with different test results.